The Construction of Kekeluargaan as an Indonesia’s Organizational Culture - Marko S Hermawan; Mark K Loo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Indonesia has the largest economy in Southeast Asia and the seventh largest GDP in the world, yet little is known about Indonesia’s organizational culture. This paper develops a deep understanding of kekeluargaan (kinship), which derives from an anthropological and sociological epistemologies. The paper explores Javanese culture as the foundation of Indonesia’s business context. A qualitative and indigenous approach was designed to determine if the kekeluargaan norm exists in the Indonesian workplace today. Document analysis and semi-structured interviews were used to collect data. The findings show that the kekeluargaan norm acts as the foundation of Indonesia’s organisational culture; with, hormat (respect) and rukun (harmony). Three proposition are given to consider the importance of understanding kekeluargaan as a salient Indonesian organizational culture. The paper concludes managerial and theoretical implications to Indonesian business context.